2014
DOI: 10.1098/rstb.2013.0179
|View full text |Cite
|
Sign up to set email alerts
|

Auditory–vocal mirroring in songbirds

Abstract: Mirror neurons are theorized to serve as a neural substrate for spoken language in humans, but the existence and functions of auditory-vocal mirror neurons in the human brain remain largely matters of speculation. Songbirds resemble humans in their capacity for vocal learning and depend on their learned songs to facilitate courtship and individual recognition. Recent neurophysiological studies have detected putative auditory-vocal mirror neurons in a sensorimotor region of the songbird's brain that plays an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 111 publications
(193 reference statements)
0
45
0
Order By: Relevance
“…Signals encoding sequential context may be conveyed from neurons in the cortical nucleus HVC that send an efference copy of premotor commands to the basal ganglia nucleus Area X (HVC X neurons) (Fee and Goldberg, 2011; Fujimoto et al, 2011; Mooney, 2014); the firing patterns of these neurons reflect not only the identity of the syllable currently being produced, but also that of preceding syllables (Fujimoto et al, 2011). Signals encoding rendition-by-rendition variation in the FF of targeted syllables are potentially generated within Area X (Woolley et al, 2014) or relayed to Area X by inputs from the motor pathway (Charlesworth et al, 2012) or LMAN (Fee and Goldberg, 2011; Kao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Signals encoding sequential context may be conveyed from neurons in the cortical nucleus HVC that send an efference copy of premotor commands to the basal ganglia nucleus Area X (HVC X neurons) (Fee and Goldberg, 2011; Fujimoto et al, 2011; Mooney, 2014); the firing patterns of these neurons reflect not only the identity of the syllable currently being produced, but also that of preceding syllables (Fujimoto et al, 2011). Signals encoding rendition-by-rendition variation in the FF of targeted syllables are potentially generated within Area X (Woolley et al, 2014) or relayed to Area X by inputs from the motor pathway (Charlesworth et al, 2012) or LMAN (Fee and Goldberg, 2011; Kao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Second, researchers have identified the song premotor region HVC as a critical structure for encoding learned song and considerable research effort has begun to elucidate how stereotyped vocal sequences are organized and represented in HVC (Amador et al, 2013; Hahnloser et al, 2002; Kosche et al, 2015; Long and Fee, 2008; Long et al, 2010; Markowitz et al, 2015; Okubo et al, 2015; Peh et al, 2015; Wang et al, 2008). Third, recent studies have revealed an essential role of song motor circuits, including HVC, in learning from sensory experience of a vocal model (Roberts et al, 2012) and indicate that sensory experience of the tutor and learning of vocal motor sequences both have a profound influence on shaping the functional organization of song motor programs during development (Adret et al, 2012; Bolhuis and Moorman, 2015; Mooney, 2014; Okubo et al, 2015; Prather et al, 2010; Roberts et al, 2012; Roberts et al, 2010; Shank and Margoliash, 2009; Vallentin et al, 2016). Songbirds have been intensively studied and we point the reader to a number of excellent reviews of songbird neurobiology (Bloomfield et al, 2011; Brainard and Doupe, 2002, 2013; Brawn and Margoliash, 2015; Doupe and Kuhl, 1999; Kuebrich and Sober, 2015; Mooney, 2014; Roberts and Mooney, 2013; Schneider and Mooney, 2015; Tschida and Mooney, 2012)…”
Section: Introductionmentioning
confidence: 99%
“…Given the complex interactions occurring during development between parents and their offspring which are so critical for song learning, it is not surprising that in songbirds, neurons with mirror properties (audio -motor mirroring) have been found. The work by Mooney and coworkers ( [33], see also [34]) clearly demonstrates that, in songbirds, areas involved in song production and learning (i.e. area HVC) do have neurons with mirror properties for audio -motor matching.…”
mentioning
confidence: 98%
“…Lesions in the HVC impair song production and song recognition, as well as the capacity to learn new contingencies. These authors suggest that audiomotor mirror neurons in songbirds may be involved in song learning and communication [34], thus making a striking parallel between the functional role of humans' Broca area in speech production and perception [35] and the HVC in birds. The possibility of investigating the molecular basis of song production and learning in different species of birds makes this model extremely promising in investigating the development and functional role of the mirror mechanism and its molecular basis.…”
mentioning
confidence: 99%